Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21203/rs.2.12798/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges and factors associated with poor glycemic control among type 2 diabetes mellitus patients at Nekemte referral hospital, western Ethiopia: cross-sectional study

Abstract: Background: Diabetes is increasing at an alarming rate throughout the world and about 80% of diabetics’ lives in developing countries. Similar to the rest of sub Saharan African countries, Ethiopia is experiencing significant burden of diabetes with increased prevalence, complications and mortality as well as life threatening disabilities. Reasons for poor glycemic control in type 2 diabetes are complex and multivariable. Hence, this study was aimed to identify challenges and factors associated with poor glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…This finding was in line with a previous studies conducted in Bangladesh (82%) 11 , India (76.6%) 13 , Asmara, Eritrea (76.7%) 16 , and Addis Ababa, Ethiopia (80%) 17 . Our finding was higher than studies conducted across Europe (37.4%) 24 , Tanzania (69.7%) 25 , Nekemte Referral Hospital (64.9%) 26 , and Gondar (60.5%) 27 . However, lower than study finding reported from India (91.8%) 28 and South Africa (86.5%) 29 .…”
Section: Discussioncontrasting
confidence: 84%
“…This finding was in line with a previous studies conducted in Bangladesh (82%) 11 , India (76.6%) 13 , Asmara, Eritrea (76.7%) 16 , and Addis Ababa, Ethiopia (80%) 17 . Our finding was higher than studies conducted across Europe (37.4%) 24 , Tanzania (69.7%) 25 , Nekemte Referral Hospital (64.9%) 26 , and Gondar (60.5%) 27 . However, lower than study finding reported from India (91.8%) 28 and South Africa (86.5%) 29 .…”
Section: Discussioncontrasting
confidence: 84%
“…Behavioral factors like smoking and alcohol drinking have a vital effect on poor glycemic control which indirectly affects the occurrence of UTIs among those diabetics. 17 Females were more likely to develop UTIs than males due to anatomic and physiologic factors 10 ; diabetic patients with high blood glucose levels, type II DM, and patients who cannot read and write have more prone to be infected. 18 A study conducted in New York showed that participants with diabetes receiving insulin therapy experience an even higher risk of infection than those not receiving insulin.…”
Section: Introductionmentioning
confidence: 99%